Human eosinophil adhesion and degranulation stimulated with eotaxin and RANTES in vitro: Lack of interaction with nitric oxide - Lintomen, Letícia; Franchi, Gilberto; Nowill, Alexandre; Condino-Neto, Antonio; de Nucci, Gilberto; Zanesco, Angelina [UNESP]; Antunes, Edson (Springer Nature, 2008)
Background: Airway eosinophilia is considered a central event in the pathogenesis of asthma. The toxic components of eosinophils are thought to be important in inducing bronchial mucosal injury and dysfunction. Previous studies have suggested an interaction between nitric oxide (NO) and chemokines in modulating eosinophil functions, but this is still conflicting. In the present study, we have carried out functional assays (adhesion and degranulation) and flow cytometry analysis of adhesion molecules (VLA-4 and Mac-1 expression) to evaluate the interactions between NO and CC-chemokines (eotaxin and RANTES) in human eosinophils. Methods: Eosinophils were purified using a percoll gradient followed byimmunomagnetic cell separator. Cell adhesion and degranulation were evaluated by measuring eosinophil peroxidase (EPO) activity, whereas expression of Mac-1 and VLA-4 was detected using flow cytometry. Results: At 4 h incubation, both eotaxin (100 ng/ml) and RANTES (1000 ng/ml) increased by 133% and 131% eosinophil adhesion, respectively. L-NAME alone (but not D-NAME) also increased the eosinophil adhesion, but the co-incubation of L-NAME with eotaxin or RANTES did not further affect the increased adhesion seen with chemokines alone. In addition, L-NAME alone (but not D-NAME) caused a significant cell degranulation, but it did not affect the CC-chemokine-induced cell degranulation. Incubation of eosinophils with eotaxin or RANTES, in absence or presence of L-NAME, did not affect the expression of VLA-4 and Mac-1 on eosinophil surface. Eotaxin and RANTES (100 ng/ml each) also failed to elevate the cyclic GMP levels above baseline in human eosinophils. Conclusion: Eotaxin and RANTES increase the eosinophil adhesion to fibronectin-coated plates and promote cell degranulation by NO-independent mechanisms. The failure of CC-chemokines to affect VLA-4 and Mac-1 expression suggests that changes in integrin function (avidity or affinity) are rather involved in the enhanced adhesion. © 2008 Lintomen et al; licensee BioMed Central Ltd.
Keywords: CD11b antigen; cyclic GMP; eotaxin; fibronectin; integrin; n(g) nitro dextro arginine methyl ester; n(g) nitroarginine methyl ester; nitric oxide; peroxidase; RANTES; very late activation antigen 4; alpha4 integrin; beta chemokine; enzyme inhibitor; cell stimulation; concentration response; controlled study; degranulation; enzyme activity; eosinophil; flow cytometry; human; human cell; immunomagnetic separation; in vitro study; incubation time; leukocyte adherence; leukocyte function; protein analysis; protein expression; protein interaction; biosynthesis; cell adhesion; cytology; eosinophilia; metabolism; physiology; Antigens, CD11b; Cell Adhesion; Cell Degranulation; Chemokine CCL5; Chemokines, CC; Enzyme Inhibitors; Eosinophilia; Eosinophils; Flow Cytometry; Humans; Integrin alpha4; Integrin alpha4beta1; Macrophage-1 Antigen; NG-Nitroarginine Methyl Ester; Nitric Oxide